VAN WYCK GRUMBACH SYNDROME INDUCED BY PRIMARY HYPOTHYROIDISM - Joshi, Nidhi; Joshi, Harish (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND We should always consider the possibility of partial or complete forms of premature puberty when dealing with primary hypothyroidism, particularly if the hypothyroidism diagnosis is delayed. Conversely, one should always keep in mind the possibility of primary hypothyroidism causing precocious puberty of the peripheral type. CASE An 8-year-old female was brought to the endocrine clinic due to short stature. She stands at 110 cm and weighs 31 kg. Her bone age was delayed by more than 2 years. Her TSH and anti-TPO antibodies were elevated. Following therapy with thyroxine 88 mcg daily, she was urgently brought to the clinic by her mother due to vaginal bleeding noted on the 25th day of thyroxine intake. She was noted to have thin-walled ovarian cysts and a thin endometrium on ultrasound indicating a peripheral type of precocious puberty. The serum estradiol and LH levels were in the prepubertal ranges. The parents were reassured and were asked to bring their daughter after 2 months for follow-up. CONCLUSION Her peripheral precocious puberty is likely due to the high TSH which can bind to the FSH receptors leading to the formation of thin-walled cysts and subsequent estradiol rise causing threshold bleeding which mimics menarche. The subsequent withdrawal of estradiol due to degenerating cysts may also trigger a random bleed. Unless there is heavy menorrhagia, specific therapy is not needed as the cysts tend to disappear spontaneously.